SKRINING KANKER PAYUDARA DENGAN SADARI PADA PUS DI DUSUN TAMBANG DESA KARANGJERUK KECAMATAN JATIREJO KABUPATEN MOJOKERTO JAWA TIMUR - Zulfa Rufaida; Sri Wardini Puji Lestari; Ika Yuni Susanti (MIDWINERSLION : Jurnal Kesehatan STIKes Buleleng, 2020)
Breast cancer is an important health problem in both developed and developing countries. The incidence and mortality rates of breast cancer can be suppressed by early detection, namely breast self-examination. The aim of community service is to increase the knowledge of pus about breast and improve the skills to do breast self-examination. The method used is the lecture method, discussion, role play and mentoring, the target is EFA in Tambang Hamlet Karangjeruk Village Jatirejo District, activities in August 2017-January 2018, analysis used frequency distribution. The results were counseling participants 22 with means of pre-test 47.8 and post-test 76.6, The results were significant there was an increase in knowledge 0,000 with a value of t = - 27,840, and 95% CI between - 31.02 - -26.71 means that the effect was strong because it did not cross the number 1 ; treatment can increase 2-3 x knowledge compared to not given. Whereas for BSE assistance, there were 33 EFA participants. Participants in breastfeeding counseling and detection with breast self-examination were enthusiastic and active in the material presented and in the discussion activities with evidence of enrichment, and during the role play activities the participants actively participated in the movements taught by the presenters. An increase in EFA knowledge about breast cancer and detection with breast self-examination. Health workers always provide information about breast cancer and breast self-examination to couples of childbearing age on an ongoing basis.